Prospects of using digital technologies in the field of combating economic crime - Budnyk , Liudmyla (Actual problems of law (Aktual’ni problemi pravoznavstva), 2026)
The article examines the current trends and prospects of implementing digital technologies in the field of combating economic offenses in Ukraine. The relevance of the research is determined by the rapid digital transformation of society and the growing complexity of economic crimes, which increasingly acquire transnational and high-tech characteristics. It is emphasized that the effective counteraction to such offenses requires innovative approaches based on the use of modern information technologies. The purpose of the study is to analyze the legal framework, current state, and practical application of digital tools—such as Big Data analytics, artificial intelligence, blockchain systems, and electronic registers—in the activities of Ukrainian law enforcement and financial monitoring institutions. Particular attention is paid to the legal regulation of electronic evidence, information security, and data protection in criminal proceedings. The research highlights the importance of digital forensics as a specialized area ensuring the detection, preservation, and analysis of electronic data while maintaining procedural integrity and evidential value. The results of the study demonstrate that the integration of digital technologies significantly increases the efficiency of investigating economic offenses by automating data processing, improving analytical accuracy, and reducing human error. Prospective directions include the implementation of electronic criminal case management systems, the use of artificial intelligence for predictive financial analytics, and the application of blockchain to enhance transparency of financial operations. The author concludes that the digitalization of law enforcement and justice processes should be grounded in the principles of legality, transparency, and international cooperation. The effective combination of legal mechanisms and technological innovation will contribute to the creation of a modern model of economic crime prevention that meets European standards and strengthens Ukraine’s economic security. The research employs methods of analysis, synthesis, and generalization to examine the current state of digital technologies in combating economic offenses. A comparative-legal and systematic approach is also applied to assess the effectiveness of implementing innovative digital tools in law enforcement practice.